2011
DOI: 10.1016/j.jbiomech.2010.10.020
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of the micro-mechanical cement–bone interface affects the cement failure in total hip replacement

Abstract: In the current study, the effects of different ways to implement the complex micro-mechanical behavior of the cement-bone interface on the fatigue failure of the cement mantle was investigated. In an FEA-model of a cemented hip reconstruction the cement-bone interface was modeled and numerically implemented in four different ways: (I) as infinitely stiff, (II) as infinitely strong with a constant stiffness, (III) a mixed-mode failure response with failure in tension and shear, and (IV) realistic mixed mode beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The location of the cracks observed in the present study (mainly proximal and distal) is consistent with previous in vitro studies . In fact, such regions are associated with higher cement stress …”
Section: Discussionsupporting
confidence: 92%
“…The location of the cracks observed in the present study (mainly proximal and distal) is consistent with previous in vitro studies . In fact, such regions are associated with higher cement stress …”
Section: Discussionsupporting
confidence: 92%
“…Finally, the fitting coefficient β was set to −0.8 (Waanders et al, 2011b). This value had to be negative in order to reproduce normal compression when loaded in pure shear.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanical characteristics of these cohesive models were based on experimental data acquired from lab-prepared cement-bone interfaces that represent the immediate postoperative situation. It has recently also been reported that the increased compliance of these lab-prepared interfaces, relative to an assumed infinitely stiff interface also increases the overall cement mantle damage (Waanders et al, 2011b). However, it is still unknown how increased compliance and reduced strength of the cement-bone interface following in vivo service influences the mixed-mode loading response and subsequent cement mantle damage.…”
Section: Introductionmentioning
confidence: 96%
“…Many studies have been performed to determine the stress distribution in the cement and at the implant -cement interface (Verdonschot and Huiskes 1997;Stolk et al 2001Stolk et al , 2003Pérez et al 2006;Waanders et al 2011). The performance of cemented THR is dependent on a number of factors including patientspecific bone geometry (Jonkers et al 2008), bone material properties (Schileo et al 2007), loading (Huiskes 1990;Pancanti et al 2003), stem design (Nicolella et al 2006;Dopico-Gonzalez et al 2010;Ishida et al 2011), stem positioning (Kleemann et al 2003;Bah et al 2011) and cement mantle thickness (Hernigou et al 2009).…”
Section: Introductionmentioning
confidence: 99%